The consequences of face-threatening feedback on innovators’ psychological safety, affect, and willingness to engage in future innovation projects - Daly, John A.; Sætre, Alf Steinar (Frontiers in Psychology, 2023)
While there is substantial research on how firms successfully end project initiativess deemed unsuitable for them very few studies focus on how leaders and managers communicate termination messages. Drawing from politeness theory and organizational support theory we explore the impact termination messages varying in face sensitivity have on innovators’ feelings of psychological safety, affect, and their willingness to continue to innovate We find that face threatening messages significantly and negatively affect innovators’ psychological safety, affect, and willingness to further innovate. The negative effects are amplified when innovators feel high commitment to their projects.